International Ethnic Networks and Intra-Ethnic Conflict - Kim, H. author. aut Link
XIII, 198 p. 6 illus.
Keywords: Since the normalization of Sino-Korean diplomatic relations in 1992, many South Koreans have moved to China for business, education, and other purposes. There they have encountered Korean-Chinese; ethnic Koreans who have lived in China for decades. This has lead to 'intra-ethnic conflict' which has divided Korean communities.